Implementasi BUDIKDAMBER untuk ketahanan pangan rumah tangga pada masa pandemi COVID-19 - Slamet Iskandar; Rina Oktasari; Agus Kharmayana Rubaya; Diana Andriyani Pratamawati (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2021)
The COVID-19 pandemic is a condition where several sectors, including the informal sector, are affected in terms of food self-sufficiency. Indirectly, the occurrence of COVID-19 as well as programs and policies to control the spread of the epidemic can cause thousands of households to experience hunger, malnutrition, to severe conditions of poverty. The purpose of this community service activity is to improve skills in utilizing yard land to produce quality, quantity and diverse food during the COVID-19 pandemic, through the application of fish bucket food “Budikdamber” by utilizing limited land to produce catfish products together with kale. Based on the activities that have been carried out, the application of “Budikdamber” benefits the community if it is carried out massively. The implementation or application of “Budikdamber” can be used as a solution to ensure food availability, especially during the COVID-19 pandemic.